HUBUNGAN TINGKAT STRES TERHADAP DISMENORE PADA REMAJA PUTRI DI MADRASAH ALIYAH MAMBA’UL ULUM AWANG-AWANG MOJOSARI MOJOKERTO - Sari Priyanti Anggraeni Devi Mustikasari (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2014)
The rate occurance dysmenorrhea in Indonesia is estimated with 55 % of women childbearing age tormented with pain during menstruation. One of factors causes dysmenorrhea is psychological. One of them is stress. The purpose of this study is to determine the relationship of stress to occurance dysmenorrhea during menstruation in adolescent girls.This research used cross sectional study. The independent variable is the level of stress and the dependent variable is dysmenorrhea in adolescent girls. The population in this study is 46 respondents. The technique is probability sampling with simple random sampling. The data are collected with a questionnaire of stress scale and occurance dysmenorrhea. The data are processed by editing, coding, scoring, tabulating. The results show that almost half of respondents who do not stress or normal consists of 18 respondents (39.1 % ) and the majority of respondents who experience dysmenorrhea amount 29 respondents ( 63.0 % ). Base on statistic test conclude that there is a correlation between the level of stress and dysmenorrhea in adolescent girls in Mamba'ul Ulum Madrasah Aliyah Awang-Awang Mojosari Mojokerto. The school should to give counseling teachers to provide guidance and counseling to the students in order to anticipate and overcome stress.